A Pseudo-Random Number Generator Based on New Hybrid LFSR and LCG Algorithm - Hameedi, Balsam Abdulkadhim; Hattab, Anwar Abbas; Laftah , Muna M. (Iraqi Journal of Science, 2022)
In many areas, such as simulation, numerical analysis, computer programming, decision-making, entertainment, and coding, a random number input is required. The pseudo-random number uses its seed value. In this paper, a hybrid method for pseudo number generation is proposed using Linear Feedback Shift Registers (LFSR) and Linear Congruential Generator (LCG). The hybrid method for generating keys is proposed by merging technologies. In each method, a new large in key-space group of numbers were generated separately. Also, a higher level of secrecy is gained such that the internal numbers generated from LFSR are combined with LCG (The adoption of roots in non-linear iteration loops). LCG and LFSR are linear structures and outputs of these Random Number Generators (RNGs) are predictable, while the proposal avoids this predictable nature. The results were tested in terms of randomness, in terms of the correlation between the keys and the effect of changing the initial state on the generated keys and the results of the tests showed that they had successfully passed the tests and resist brute force and differential attack.